School administrators' leadership in curriculum implementation of Tahfiz Model Ulul Albab (TMUA): a case study - Md Ali, Nurul Jawahir; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study used a qualitative approach to explore the school administrators’ leadership in curriculum implementation of Tahfiz Model Ulul Albab (TMUA). The study also aims to identify the arising issues and strategies used by the administrators in leading the implementation of the curriculum. This research is a case study that was conducted in a National Secondary Religious School (SMKA) involving 3 participants, namely the Principal, Senior Assistant 1 and Coordinator of TMUA. The data were collected through interviews, observations and document analysis. The findings show that there are several emerging themes found in administrators’ leadership in curriculum implementation, which are ‘understanding’, ‘goal setting’, ‘instructional management’, ‘teacher development’, ‘rabbani/religious influence’, ‘sharing of responsibility, and ‘networking’. Challenges and strategies in leading the curriculum implementation consists of three categories, namely ‘issues of system and technical’, ‘issues of teacher’, and ‘issues on student performance’. This research shows the discovery of new dimensions in school administrators’ leadership. This study implies that the implementation of a new curriculum is challenging and requires meticulous planning on the part of the policy maker as well as effective administration and management by school administrators.